2018
DOI: 10.1063/1.5021023
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced optical-to-THz conversion efficiency of photoconductive antenna using dielectric nano-layer encapsulation

Abstract: Photoconductive antennas (PCAs) are among the most conventional devices used for emission as well as detection of terahertz (THz) radiation. However, due to their low optical-to-THz conversion efficiencies, applications of these devices in out-of-laboratory conditions are limited. In this paper, we report several factors of enhancement in THz emission efficiency from conventional PCAs by coating a nano-layer of dielectric (TiO2) on the active area between the electrodes of a semi-insulating GaAs-based device. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…By coating an 80 nm nano-layer of dielectric (TiO 2 ) on the active area between the electrodes of a semi-insulating GaAs-based device, shown in Fig. 11, the reflection from the Si-GaAs interface was suppressed by~6.9% [68]. In 2019, Kazemi et al used mixed graphene-gold electrodes as electrode material of the antenna, which enhanced the detected THz signal peak amplitude up to 14.31% [69].…”
Section: Optimization Of Thz Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…By coating an 80 nm nano-layer of dielectric (TiO 2 ) on the active area between the electrodes of a semi-insulating GaAs-based device, shown in Fig. 11, the reflection from the Si-GaAs interface was suppressed by~6.9% [68]. In 2019, Kazemi et al used mixed graphene-gold electrodes as electrode material of the antenna, which enhanced the detected THz signal peak amplitude up to 14.31% [69].…”
Section: Optimization Of Thz Systemmentioning
confidence: 99%
“…13(a) which generate THz powers in the milliwatt range and exceed the Manley-Rowe limit for frequencies less than 2 THz [74]. In 2020, Koulouklidis et al demonstrated two-color filamentation of femtosecond mid-infrared laser pulses at 3.9 μm generating ultrashort [68] sub-cycle THz pulses with sub-milijoule energy. The results showed THz conversion efficiency of 2.36%, resulting in THz field amplitudes above 100 MV cm − 1 [75].…”
Section: Optimization Of Thz Systemmentioning
confidence: 99%
“…Recently, a highly electrical resistive TiO 2 was proposed as an antireflection coating in contrast to the above-mentioned materials. 105 The schematic view and an SEM image of the proposed PCA with a TiO 2 layer with its spectral characteristics are depicted in Fig. 9.…”
Section: Dielectric Metasurfacesmentioning
confidence: 99%
“…4 To meet the aforementioned substrate requirements, the preferred choices for PCAs are LT-GaAs, [11][12][13] SI-GaAs, 13,14 and In-GaAs. 13,15 The suggested approaches for the enhancement of the IR coupling to PCA include antireflection coatings 16,17 and the usage of micro lens arrays. 9,11,12,16,18,19 The poor directivity issue of the PCA at room temperature is being addressed by integrating the lens shape on the back of the antenna structure 9,16,[20][21][22] and combining antenna with the metasurfaces.…”
Section: Introductionmentioning
confidence: 99%
“…13,15 The suggested approaches for the enhancement of the IR coupling to PCA include antireflection coatings 16,17 and the usage of micro lens arrays. 9,11,12,16,18,19 The poor directivity issue of the PCA at room temperature is being addressed by integrating the lens shape on the back of the antenna structure 9,16,[20][21][22] and combining antenna with the metasurfaces. 10,20 The large area emitters are also reported in literature for the reduction of saturation effects of the optical pump.…”
Section: Introductionmentioning
confidence: 99%